Respuesta :

Answer:X= -4

Step-by-step explanation:

6 less than the product of a number and 3 is -18.

Make each part of the sentence into numbers:

"the product of a number and 3":  becomes X*(3), where X is the "number."

"6 less than":  is -6, so we have:

X*(3) - 6

"is -18"  means = -18

Put the segments into one equation and solve:

X*(3) - 6 = -18

3X-6=-18

3X = -12

X = -4

====

See if this works:  If X=-4, then the product of it and 3 is -12.  Six less than -12 is -18.  And that is correct.  X= -4